Thermal limits of bumblebees and honeybees are modulated by different functional traits: predictions of a mechanistic model - Sarah A. MacQueen; Dara A. Stanley; Jon M. Yearsley (PLoS ONE, 2025)
Local weather conditions are expected to have species specific effects on the activity of insect pollinators. However, the relationship between changing weather patterns and pollinator activity has not been well studied. We develop a thermodynamic model for insect thorax temperature that provides a mechanistic link between local weather conditions and functional traits (e.g. body mass, flight speed) and flight activity. We show that behavioural warming and cooling adaptations are essential for temperate bumblebees and the western honeybee, and that the maximum air temperature for sustained flight depends primarily on flight speed for honeybees, whereas for bumblebees it depends upon both flight speed and thorax mass. Our results suggest that the activity of these two pollinator groups will respond differently to climate change, and that different bee groups may provide a compensatory role for each other in different weather conditions. Thus, both are important for sustained crop pollination under future change.